Nieposłuszeństwo i profanacje – globalne społeczeństwo obywatelskie - Pietrzak, Edyta (Przegląd Politologiczny, 2018)
Transnational space provides the framework for discussing the topics of this paper: civil society, civil disobedience and the concept of profanation developed by the Italian philosopher Giorgio Agamben. The first two topics are mutually related, whereas the third one expands the former two and challenges them with the tasks to be performed by both politically aware social movements and authorities. The paper attempts to answer the question of what outcomes this challenge produces.